Application of Open-Ended Coaxial Sensor to Determine Oil Palm Fruit Ripeness - You, Kok Yeow (2006)
This thesis presents a critical study on the use of an open-ended coaxial sensor for the determination of both complex permittivity and moisture content of oil palm fruits of various degrees of fruit ripeness at ()125±oC. The sensor was studied based on the calculation of reflection coefficient using an integral admittance approach and finite element method (FEM). In this work, the computation of reflection coefficient of the oil palm fruits was realized using MATLAB and FEMLAB GUI software for the admittance approach and finite element method (FEM), respectively. The results were compared with the measured reflection coefficient using the open-ended coaxial sensor in conjunction with a HP8720B vector network analyzer (VNA). The sensor operating between 1 GHz and 5 GHz was fabricated from a 4.1 mm outer diameter sub-miniature A type (SMA) coaxial tub contact panel. The measuring end of the sensor was calibrated by a transmission line procedure. The integral admittance formulation was simplified into a series expression. The local truncation errors of the series approximation were critically analyzed. The two-dimensional FEM was used to solve the rotationally symmetric region of the open-ended coaxial line. The FEM results are closed to the measurements data than calculated admittance formulation. The maximum absolute errors of FEM and measurement results for magnitude and phase reflection coefficient are less than 0.02 and 0.1 rad, respectively, compared with 0.05 and 0.2 rad of admittance formulation and measurement results, respectively. However, the results were in good agreement that the minimum thickness of a sample under test is 2 mm. An inverse solution based on two admittance models (lumped-parameter admittance and integral admittance formulations) has been utilized to derive complex permittivity from measured reflection coefficient. The lumped-parameter admittance or closed form capacitance model is simpler in the calculation than integral admittance model. Unfortunately, it is not accurate for high operating frequencies (>5 GHz). However, the permittivity results from both models agree with measured data using HP 85070B coaxial probe and publish values (Cole-Cole model) ranging 1 GHz to 5 GHz. A calibration equation has been developed based on the relationship between the measured moisture content obtained by the oven drying method and the phase of the reflection coefficient of the sensor. The moisture content predicted by the sensor was in good agreement with those obtained using the standard oven drying method with its absolute error within 5 % moisture content, when tested on 145 different fruits samples. A model detailing two dielectric relaxation process parameters was proposed in order to represent the permittivity of oil palm mesocarp based on measured data using HP 85070B coaxial probe from 0.13 GHz to 20 GHz. The model successfully estimated the complex permittivity for various ripeness stages of oil palm mesocarp as a function of frequency, moisture and ionic conductivity, as well as the bulk density. A dielectric measurement software has been developed to control and acquire data from the VNA using Agilent VEE. The software is also used to calibrate measurement at the aperture plane of sensor and to calculate the complex permittivity from the measured reflection coefficient between 1 GHz and 5 GHz.